Análisis y desarrollo de un prototipo de un servidor web para la Unidad Educativa del Milenio Carlos Alberto Aguirre Avilés, en la Parroquia La Unión - Carrasco Palacios, Jesús Alberto (2021)
The Millennium Educational Unit "Carlos Alberto Aguirre Avilés" does not have a web server capable of performing multiple tasks that facilitate the work of administrative and teaching staff, and in turn students can review information such as mission, vision and activities, with the purpose of benefiting the educational community. The objective of this Case Study is to develop a web page prototype for the institution "Carlos Alberto Aguirre Avilés", based on the analysis in relation to the needs and interests present in the institution. The design of a prototype of a web page for the educational unit of the Millennium "Carlos Alberto Aguirre Avilés" could be carried out thanks to all the analysis that was carried out, as well as the descriptive study and the methodological field. As a result of the investigation, it was determined that the institution has shortcomings in relation to technological means, specifically in the lack of a web page, a problem that causes that, on many occasions, especially now in the pandemic, there are relationship problems between parents of families and institution. The creation of a web page will be a great educational resource, this page will serve for the dissemination of institutional information, the execution of errands, download documents, students' grades, the presentations of the professional team of teachers in classes, the knowledge of the activities of the Educational Unit and will also allow parents, students and other users to be at the forefront of the activities developed in the academy.